Homophobic hate discourse in the information society: from the impacts to the balance of the computer environment and to human sexuality - Cazelatto, Caio Eduardo Costa; Cardin, Valeria Silva Galdino (Revista do Direito, 2017)
The changes arising from the techno scientific evolution have impacted the social model, fomenting the emergence of the Information Society and a computer-based environment. Along with these novelties, the discourse of hate, especially homophobic, has gained a new platform for it to spread, becoming responsible for violating the rights of sexual minorities. The objective of this research was to analyze, through the theoretical method, the discourse of homophobic hate as a degrader of the computer's environmental balance, as well as towards the exercise of human sexuality. In order to do so, we explored the Computer Society within the juridical-constitutional realm of the digital scope, listing it as an extension of the cultural environment. In addition, freedom to sexuality was defined as a right of personality, where the heteronormativity, based on homophobia, is materialized in a discourse of hate, solidifying prejudice, intolerance and discrimination towards the LGBTQ community. For this, we verified that the abuse towards the right to freedom of expression constitutes discursive acts of hate, manifested in social exclusion of sexual minorities, far from being a mere opinion.